L’intégration de la sécurité lors de la conception de machines à risques pour les opérateurs : comparaison de logiques différentes de conception - Cécilia De la Garza (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study is in the field of work equipment design. The aim was to identify effective methods of integrating safety. Two types of integration were identified in the activity analysis : « direct means » and « indirect means ». The first relates to normative and regulatory aspects and the second to explicit or implicit individual knowledge about the actual use of the equipment. Comparison of two design projects during the testing phase in two different design companies shows a different integration of safety. In the first case, only direct ways existed, linked to a functioning logic. In the second case, utilization logic is involved in certain production and maintenance operations being considered in the design choices. Nevertheless, in both cases, these safety integration methods cover only part of upstream prevention and are not systematic. Safety integration appears more as an obligation than as an investment and is not integrated into the specifications with the same status as technical performance criteria and performance objectives. It is included during the design process in a nonsystematic way. Deficiencies in safety will then promote system migration during operation towards less certain areas and lead to accidents or to boundary activities tolerated with use.